The Christian doctrine of the divine attributes - Cremer, Hermann, 1834-1903.; Price, Robert B.; Burkhardt, Helmut; Gockel, Matthias (Eugene, Oregon : Pickwick Publications, 2016)
Cremer's short, energetic treatise on the divine attributes was admired by both Karl Barth and Wolfhart Pannenberg. Cremer chastises the speculative flights of traditional doctrines of the divine attributes and issues a resounding summons to a more exegetically, economically, and christologically grounded account. Known primarily as a biblical scholar for his Biblico-Theological Lexicon of New Testament Greek, precursor to the monumental TDNT, Cremer shows himself here also an able systematician, with a pastor's eye for the role played by doctrine in the life of congregational and individual faith.
The concept of the divine attributes -- The derivation and classification of the attributes -- First series -- Second series -- The unity of the divine attributes, or the glory of God.
Print version record.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Divinity; Jesus Christ -- Natures; God (Christianity) -- Attributes; Revelation -- Christianity; Theology, Doctrinal; RELIGION -- Christian Theology -- Christology; Jesus Christ; Divinity of Christ; God (Christianity) -- Attributes; Natures of Jesus Christ; Revelation -- Christianity; Theology, Doctrinal; Electronic books